Celiac disease - Kelly, Ciaran (Henry Stewart Talks, 2011)
Changing estimates of disease prevalence, Clinical spectrum of celiac disease, Approach to diagnosis, Serology testing, Histopathology in diagnosis, Management, Non-responsive celiac disease, Refractory celiac disease types I and II
Reviewed at 2022/04/12